AIT :
Continued by: Information A.I.T. (ZF 60864). - See also: A.I.T. Organe de l'Association internationale des travailleurs (ZF 30029), A.I.T. Bulletin d'information ... (ZK 30080), A.I.T. El boletin ... (ZK30080), A.I.T. Organo de la Asociacion ... (ZF 30029).